Medical checkup, medical treatment and athlete rehabilitation in sports clinic, medical center, JISS - Hangai, M.; Suzuki, A. (Journal of High Performance Sport, 2020)
The Sports Clinic at Japan Institute of Sports Sciences (JISS) Medical Center has three main roles to conduct medical checkups, medical treatments and athlete rehabilitation. Our clinic has been accepting Paralympic athletes who do not need special care and daily medical care and have highly medal potential for Paralympic Games since 2016. The number of Paralympic athletes who visit our clinic is increasing year by year. Medical checkup for Paralympic athletes, contains both the screening items which JISS had determined for Olympic athletes and the screening items which Japanese Paralympic Committee (JPC) require to certify athletes for annual screening.We do not distinguish doctors and hours of consultation for their medical treatments between Paralympic athletes and Olympic athletes. By March 2018, the athletes of 15 Paralympic sports have visited our clinic. We respond to the problems unique to Paralympic athletes, such as urinary tract infections that are common in Paralympic athletes and questions about the impairment they have. We also try to create the medical diagnostics forms for their classification as much as possible. If necessary, they are introduced to athlete rehabilitation and nutrition consultation in our medical center. The support from the specialists and the primary care doctors are indispensable as there are some limitations at the JISS Medical Center. With their support, we will continue to support Paralympic athletes on the basis of understanding their impairments and their sports characteristics.